Integrating Arab Cultural Elements in Arabic Language Education - Sulton, Achmad; Kabir, Saleh Muhammad (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2025)
This study investigates the integration of Arab cultural elements into Arabic language education in Indonesia, focusing on its impact on student engagement, vocabulary acquisition, and communicative competence. Data were collected through classroom observations, semi-structured interviews with Arabic teachers, focus group discussions with students, and document analysis. The findings reveal that incorporating cultural elements—such as traditional Arabic greetings, oratory practices (khitabah), poetry, culinary activities, and religious expressions—enhances student motivation, lowers anxiety, and fosters a more immersive and meaningful learning environment. The study concludes that integrating cultural content is not merely an aesthetic addition, but a pedagogical necessity that promotes contextualized and emotionally resonant Arabic language instruction. This research contributes to a growing body of literature advocating for intercultural and humanistic approaches in Arabic language pedagogy, particularly in non-Arabic-speaking contexts such as Indonesia.